Enhanced volatile phenols in wine fermented with Saccharomyces cerevisiae and spoiled with Pichia guilliermondii and Dekkera bruxellensis - Sáez, J. S. (2010)
Aims: To investigate whether the presence of Pichia guilliermondii impacts on theproduction of volatile phenols from mixed wine fermentations with Dekkerabruxellensis and Saccharomyces cerevisiae.Methods and Results: Four inoculation strategies were performed in small-scalefermentations involving P. guilliermondii, D. bruxellensis and S. cerevisiae usingSyrah grape juice supplemented with 100 mg l)1 of p-coumaric acid. Highpressure liquid chromatography was used for the quantification or volatile phenols.Significant high levels of 4-ethylphenol and 4-ethylguaicol (720 and545 lg l)1, respectively), as well as the highest levels of 4-vinylphenol(>4500 lg l)1), were observed when P. guilliermondii species was inoculatedfrom the beginning of the fermentation.Conclusions: The metabolic interaction occurring between the high vinylphenolproducer species P. guilliermondii and D. bruxellensis exhibiting a high vinylphenolreductase activity resulted in an increased production of volatilephenols in wine.Significance and Impact of the Study: Pichia guilliermondii must be considereda very important spoilage yeast in the wine industry capable of producing largeamounts of volatile phenols.